Advances in the economic analysis of participatory & labor-managed firms. Vol. 16 - Kauhanen, Antti (Emerald, 2015)
Alternative types of ownership and participatory managerial practices have recently been intensively debated. The great recession has revived interest in cooperative and labor-managed organizations. In addition, employee participation in decision-making and financial performance has consistently attracted attention during the last 20 years. The articles in this volume contribute to both of these topics. The first set of articles studies the relationship among business cycles, alternative forms of ownership, and employee voice. These papers take various theoretical and empirical approaches and investigate many industries and countries. They show how the economic downturn is leading to increased incidence of employee ownership but also undermining employee voice by increasing the incidence of atypical employment. The second set of papers looks inside firms. The topics include the relationship between ownership and innovation and how financial participation and group incentives affect employee attitudes and work effort. The contributions in this volume provide stimulating research in the broad area of participatory and labor-managed organizations.
Keywords: Management -- Employee participation.; Employee empowerment.; elektronické knihy; electronic books